Hubungan Jaminan Persalinan, Jarak Tempat Tinggal, Waktu Tempuh dan Kebiasaan Masyarakat Terhadap Pemanfaatan Tempat Persalinan Di Kabupaten Timor Tengah Selatan - Mareta Bakale Bakoil; Stefanus Supriyanto; Toetik Koesbardiati (JURNAL INFO KESEHATAN, 2017)
Background: The phenomenon in Indonesia is still the number of mothers giving birth does not use health facilities and with the help of non-health workers, which can affect the high maternal mortality rate. South Central Timor District is one of the regencies in East Nusa Tenggara province with the highest maternal mortality rate of 290/100,000 live births. In addition, the problem of access to health facilities is low, due to the affordability of locations where health services are difficult, the type and quality of service and affordability to information (WHO, 2008). Methods: observational analytic with a cross-sectional design. The number of sample of 95 respondents. Sampling technique is systematic random sampling. Data analysis using SPSS. Descriptive analysis to describe the frequency distribution of each variable, the chi-square test used for bivariate analysis is to assess the relationship between independent variables with a dependent. Statistical test with a 5% significance level. Result: labor guarantee has p-value 0,003 (OR 0,098, 95% CI: 0,019-0,509), distance of residence with p-value 0,498 (OR 1,822 95% CI 0,428-7,761), travel time with p-value 0,710 (OR 1,292 95% CI 0.299-5,583), community habits in choosing the birthplace with p-value 0.010 (OR 13.833 95% CI 2,282-83,861). Multivariate analysis showed that labor delivery and community habits in choosing delivery sites were the strongest determinants of the utilization of maternity sites compared to other variables. Conclusions: Guaranteed labor and community habits in choosing a delivery venue have a significant relationship with the utilization of delivery at health facilities. While the distance between the residence and the travel time is not significant to the utilization of delivery places in health facilities.